Patients With Bicuspid Aortic Stenosis Undergoing Transcatheter Aortic Valve Replacement: A Systematic Review and Meta-Analysis - Zhang, Yi; Xiong, Tian-Yuan; Li, Yi-Ming; Yao, Yi-Jun; He, Jing-Jing; Yang, Hao-Ran; Zhu, Zhong-Kai; Chen, Fei; Ou, Yuanweixiang; Wang, Xi; Liu, Qi; Li, Xi; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective: We sought to conduct a systematic review and meta-analysis of the clinical adverse events in patients undergoing transcatheter aortic valve replacement (TAVR) with bicuspid aortic valve (BAV) versus tricuspid aortic valve (TAV) anatomy and the efficacy of balloon-expandable (BE) versus self-expanding (SE) valves in BAV population. Comparisons will be stratified into early and new generation devices. Differences of prosthetic geometry on computed tomography (CT) between BAV and TAV patients will be presented. In addition, BAV morphological presentations in studies included will be summarized. Method: Observational studies and a randomized controlled trial of patients with BAV undergoing TAVR were included according to PRISMA guideline. Results: A total of 43 studies were included in the final analysis. In patients undergoing TAVR, type 1 BAV was the most common phenotype while type 2 BAV accounted for the least. Significant higher risks of conversion to surgical aortic valve replacement (SAVR), need of a second valve, moderate or severe paravalvular leakage (PVL), device failure, acute kidney injury (AKI), and stroke were observed in BAV than TAV patients during hospitalization. BAV had higher risk of new permanent pacemaker implantation (PPI) both at hospitalization and 30-day follow-up. One-year mortality in BAV was significantly lower than that in TAV (OR = 0.85, 95% CI 0.75 - 0.97, p = 0.01). BE THVs had higher risks of annular rupture but lower risk of need of a second valve and new PPI than SE THVs. Moreover, BE THV was less expanded and more elliptical in BAV than TAV. In general, rates of clinical adverse events were lower in new generation THVs than the early both in BAV and TAV. Conclusions: Although with higher risks of conversion to SAVR, need of a second valve, moderate or severe PVL, device failure, AKI, stroke and new PPI, TAVR seems to be a viable option for selected patients with severe bicuspid aortic stenosis, which demonstrated potential benefit of 1-year survival, especially among lower surgical risk population using new generation devices. Larger randomized studies are needed to guide patient selection and verified the durable performance of THVs in BAV population.